Effects of Meloxicam on Oxidative Stress in Calves Undergoing Dehorning with Caustic Paste - Yakan, Selvinaz; Burak, Şemsettin (Acta Scientiae Veterinariae, 2026)
Background: Dehorning is a common practice in cattle operations aimed at enhancing animal safety, reducing the risk of injury to other animals and humans, and limiting aggressive behaviors. All dehorning methods, including thermal, surgical, and caustic paste application, cause pain, stress, and physiological changes in the animals. Non-steroidal anti-inflammatory drugs (NSAIDs), particularly meloxicam, are used to alleviate pain and inflammation associated with the procedure. This study aimed to investigate the effect of dehorning using the caustic paste method, with and without the administration of painkillers, on both clinical indicators and blood parameters in calves. Materials, Methods & Results: The study involved 24 calves, arbitrarily divided into 2 groups, each comprising 12 calves. In group I, each calf received an intravenous (IV) dose of 2.2 mg/kg of meloxicam dispensed 30 min before dehorning, followed by caustic paste for horn blunting. In group II, the calves' horns were blunted using the same technique but without administering analgesia. Blood samples were collected at 0, 15, 30, and 60 min from calves in both groups, and clinical observations were documented. Cortisol levels (measured via ELISA), glucose levels (measured via ELISA), total oxidant capacity (TOC), total antioxidant capacity (TAC) (measured via ELISA), and glutathione (GSH) levels (measured via ELISA) were assessed in the collected blood samples. Cortisol levels in Group I showed a significant reduction at 15, 30, and 60 minutes compared to baseline (P < 0.001), whereas no significant changes were observed in Group II throughout the measurement times (P > 0.05). Glucose levels in Group I were lower than those in Group II at 30 and 60 min; however, the difference was not statistically significant (P > 0.05). When evaluated in terms of oxidative stress parameters, Group I showed significantly lower total oxidant capacity (TOC) values (P < 0.001) and total antioxidant capacity (TAC) values (P < 0.05) compared to Group II, whereas glutathione (GSH) values were higher (P < 0.001). These findings indicate that administering analgesics before dehorning reduces cortisol levels, alleviates oxidative stress, and supports the antioxidant system. Discussion: Dehorning is an economically significant practice in cattle operations; however, it induces considerable stress, particularly in adult animals. Performing the procedure as early as possible, within the 1st 2 months after birth, minimizes discomfort in the animals. The method used also represents a key factor affecting stress levels; in calves aged 8-14 days, the caustic paste method emerges as the least painful and most practical approach. In this study, physiological parameters (heart rate, respiratory rate, and rectal temperature) generally remained within reference ranges, with a brief increase in heart rate indicating acute stress. In the group receiving meloxicam, lower cortisol and glucose levels demonstrated that analgesia effectively reduces pain-induced stress and inflammation. Regarding oxidative stress parameters, TOC decreased, while TAC and GSH levels increased in the analgesia group. Conversely, opposite trends were observed in the non-analgesia group, indicating higher stress and oxidative load in animals that did not receive analgesic treatment. In conclusion, the use of sedation and local anesthesia combined with analgesia effectively alleviates pain and stress during caustic paste dehorning, rendering this method a safe, effective, and practical procedure for calves. Keywords: dehorning, meloxicam, oxidative stress, calves.